Characteristics of Endothelial Permeability in Tumours and the Role of Neutrophils - Cindric, Suzana (My University, 1996)
Vascular hyperpermeability is a common characteristic among many tumour types, especially those that grow in ascites form. With these, the exudate that flows out of the circulation collects as ascites fluid in the cavities within which these tumours are growing. In the past, this hyperpermeability has been attributed to the production of vascular permeability factor (VPF) by tumours. VPF has been found to bind to endothelial cells and lead to an increased vascular permeability. In the present study, the role of polymorphonuclear leukocytes (neutrophils) in tumour vascular hyperpermeability was investigated. Hey-3 tumour cells were grown into masses on the chick embryo chorioallantoic membrane (CAM). Interstitial neutrophilia was found to be a common feature at the tumour-host interface. Horseradish peroxidase was injected into the circulation and allowed to perfuse for five minutes. The density of labelled vesicles within the endothelial cell cytoplasm was calculated to be 0.99 +/-0.28 vesicles/μm². This vesicular density was comparable to that of N-formyl-methionine-leucine-phenylalanine (a chemotactic peptide for neutrophils)-treated CAM (1.04 +/-0.09 vesicles/μm²), but very different from control CAM (0.51 +/- 0.09 vesicles/μm²). In order to rule out any immune response to foreign cells, immune hepatocyte masses were grown on the CAM and vesicular density was calculated to be 0.54 +/-0.03 vesicles/μm². Through chemotaxis assays with the Boyden chamber, it was observed that Hey-3 tumour cells in culture were producing a chemotactic factor that is an attractant for human neutrophils. Once in the area, neutrophils do possess the potential to increase vascular permeability. Thus, neutrophils play a role in vascular endothelial hyperpermeability in tumours.
Endothelial Permeability in Tumours
Keywords: endothelial; permeable; tumour; neutrophil